CD57 Expression in Incidental, Clinically Manifest, and Metastatic Carcinoma of the Prostate. (22nd May 2014) - Wangerin, Holger; Kristiansen, Glen; Schlomm, Thorsten; Stephan, Carsten; Gunia, Sven; Zimpfer, Annette; Weichert, Wilko; Sauter, Guido; Erbersdobler, Andreas
Abstract : Objectives . CD57 is normally found on NK-cells, but little is known about its expression in prostatic tissue. Methods . We investigated CD57 expression by immunohistochemistry using tissue microarrays containing 3262 prostate cancers (PCa), lymph node metastases, and benign prostatic tissue. The results were compared with clinical and pathological parameters. Results . Overall, 87% of PCa showed a moderate or strong expression of CD57. There was no significant difference to corresponding benign prostatic tissue. CD57 was increasingly lost from incidental over clinically manifest cancers to metastases. It correlated significantly with Gleason grade and pT-category, but not with PSA tissue expression. Loss of CD57 expression was an independent risk factor for PSA recurrence after prostatectomy in a multivariate Cox regression analysis. In standard sections, CD57 expression was heterogeneous, especially in large, high-grade PCa. Conclusions . There is a peculiar expression of CD57 in PCa and benign prostatic tissue. CD57 loss is associated with tumor dedifferentiation and tumor size. However, the use of this marker for prognostic purposes is hampered by its heterogeneous expression.